Highlights from the LHCb experiment - Winn, Michael (Nuclear physics. A, Nuclear and hadronic physics, 2019)
We report recent results by the LHCb collaboration in heavy-ion collisions in collider and fixed-target mode at the LHC. A large variety of measurements show the potential of LHCb in nuclear collisions.
XXVIIth International Conference on Ultrarelativistic Nucleus-Nucleus Collisions (Quark Matter 2018)
Gesehen am 26.11.2019